PRESCRIPTION COMPLETNESS FOR MALARIA PATIENTS AT ABEPURA COMMUNITY HEALTH CENTER, JAYAPURA CITY - Dzukharian Munandar; Brechkerts Lieske Angruni Tukayo; Rahayu Samalo; Mersi Naomi Rumayomi (GEMA KESEHATAN, 2022)
A prescription, according to the definition based on the Minister of  Health, is a request written by a doctor or dentist to a pharmacist to prepare and deliver drugs to patients according to applicable regulations. Before submitting a prescription, it is necessary to examine administrative, pharmaceutical, and clinical aspects to reduce medication errors and increase patient safety rates. This study aims to describe the completeness of prescriptions for malaria patients at the Abepura Health Center. This type of research was descriptive, with secondary data collection from malaria patient prescriptions for one month. The study's results obtained 169 pills and grouped by age; the highest was in the 17-25 year age group with 50 patients (29.6%). Malaria sufferers were dominated by men, namely 110 patients (65%). According to the completeness of prescriptions, regarding patient data, 157 pills (93%) were complete; regarding doctor data, 169 medicines were incomplete (100%); regarding drug data, 112 prescriptions (66.3%) were done; and other administrative related data were 169 prescriptions. Complete (100%). Medicines for patients with malaria at the Abepura Health Center are not exclusive. Keywords: Complete prescriptions, Community health center, Malaria prescriptions